Pengaruh Kebijakan Dividen, Keputusan Investasi, dan Struktur Modal Terhadap Nilai Perusahaan Perbankan Konvensional di Indonesia - Nastiti, Putri Ayu; Triono, Hermawan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to evaluate the impact of profit distribution policy, investment allocation decisions, and capital structure composition on firm value in the conventional banking sector listed on the Indonesia Stock Exchange during the 2020–2023 period. The research focuses on the urgency of enhancing firm value as a reflection of investor confidence and as a determinant of sustainable competitiveness in an increasingly dynamic banking environment. A quantitative approach was employed, applying multiple linear regression analysis. The data were obtained from the annual financial reports of 12 listed conventional banks. The research findings indicate that dividend policy (H1) has a positive and significant effect on firm value, meaning that the more optimal the dividend distribution policy implemented, the higher the firm value. Investment decisions (H2) also have a positive and significant effect on firm value, suggesting that the more precise the investment decisions made, the greater their contribution to enhancing firm value. Furthermore, capital structure (H3) has a positive and significant effect on firm value, indicating that proportional management of the capital structure can increase investor confidence and drive firm value growth.